2015
DOI: 10.1007/s13277-015-3494-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of toll-like receptors in HPV-positive and HPV-negative oropharyngeal squamous cell carcinoma—an in vivo and in vitro study

Abstract: The incidence of oropharyngeal squamous cell carcinoma (OPSCC) has increased over the past decades in many western countries. This trend is mainly attributed to the human papillomavirus (HPV). Cancer-related actions of immunological defense systems are being intensively researched. Human toll-like receptors (TLRs) are a family of pattern recognition receptors that participate in the immunological defense against pathogens, but their actions are also linked to cancer. The expression of TLRs in cervical epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 52 publications
4
35
0
3
Order By: Relevance
“…in a specific subtype of OPSCC), as has been previously shown in HPV þ and HPV À OPSCC and whether TLR5 and TLR7 expression would correlate with survival in HPV þ BOTSCC [15]. Our results confirmed that absent/weak TLR5 and medium/strong TLR7 expression was more frequently found in HPV þ compared with HPV À BOTSCC [15,20]. However, it was not possible to confirm with statistical significance that moderate/strong TLR5 or absent/weak TLR7 expression would correlate with worse outcome irrespective of tumor HPV status.…”
Section: Discussionsupporting
confidence: 89%
“…in a specific subtype of OPSCC), as has been previously shown in HPV þ and HPV À OPSCC and whether TLR5 and TLR7 expression would correlate with survival in HPV þ BOTSCC [15]. Our results confirmed that absent/weak TLR5 and medium/strong TLR7 expression was more frequently found in HPV þ compared with HPV À BOTSCC [15,20]. However, it was not possible to confirm with statistical significance that moderate/strong TLR5 or absent/weak TLR7 expression would correlate with worse outcome irrespective of tumor HPV status.…”
Section: Discussionsupporting
confidence: 89%
“…The histopathological tissue blocks of primary tumors and neck recurrences were obtained to study protein p16 expression. We used the tissue microarray (TMA) method for primary tumors and whole tissue blocks for regional recurrences, as described elsewhere . For TMA analysis, 3 samples were taken from each tumor.…”
Section: Methodsmentioning
confidence: 99%
“…We used the tissue microarray (TMA) method for primary tumors 13 and whole tissue blocks for regional recurrences, as described elsewhere. 14 3 | R E S U L T S…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Ainda existem muitas contradições e mais estudos são necessários. Em cabeça e pescoço, existe apenas um estudo(68) avaliando alguns dos receptores Toll-likes. Este é o primeiro estudo em orofaringe avaliando todos os 10 TLRs e a função dos principais receptores.…”
unclassified
“…Em carcinoma de colo de útero, estudos demonstraram aumento da expressão de TLR9 em mulheres que apresentavam HPV persistente (67) e em mulheres que apresentavam eliminação do vírus(9). O aumento de TLR9 é devido ao reconhecimento do vírus pelo receptor e consequente ativação do sistema imune para a tentativa de eliminação do vírus.Entretanto, o estudo realizado com CECOF HPV+ demonstrou diminuição de TLR9(68), assim como outros estudos com carcinoma de colo de útero, demonstraram que TLR9 apresentava baixa expressão. Esta diminuição ocorre como forma de escape do HPV do sistema imune e persistência na célula.…”
unclassified